Influence of silica nanoparticles functionalized with poly(butyl acrylate‐co‐glycidyl methacrylate)‐g‐diaminodiphenyl sulfone on the mechanical and thermal properties of bismaleimide nanocomposites. Issue 12 (23rd August 2013) - Xiong, Lei; Lian, Zeyang; Liang, Hongbo; Huang, Shengmei; Fan, Hongqing
<x xml:space="preserve">Abstract</x> The silica nanoparticles functionalized with poly(butyl acrylate‐co‐glycidyl methacrylate)‐g‐diaminodiphenyl sulfone (P(BA‐co‐GMA)‐g‐DDS)) were prepared via atom transfer radical polymerization and ring open reaction, and characterized by Fourier transform infrared and X‐ray photoelectron spectroscopy. Subsequently, the influence of SiO2 content on the mechanical and thermal properties for the bismaleimide (BMI) resin nanocomposites modified with pristine SiO2 and SiO2‐P(BA‐co‐GMA)‐g‐DDS) was investigated. It was found that SiO2‐P(BA‐co‐GMA)‐g‐DDS) was more effective as a modifier than pristine SiO2. The most significant improvement of the impact strength (+108.7%) and flexural strength (+64.5%) was obtained with SiO2‐P(BA‐co‐GMA)‐g‐DDS) at 0.5 wt% content. Moreover, the thermal properties of nanocomposites were distinctly improved with the addition of functionalized SiO2. The reasons for these changes were discussed in this article. POLYM. COMPOS., 34:2154–2159, 2013. © 2013 Society of Plastics Engineers